Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
Assuming that the x2 is x squared, B
Step-by-step explanation:
(1)(1) + 5(1) - 6 = 1 + 5 - 6 = 6 - 6 = 0
(-6)(-6) + 5(-6) - 6 = 36 - 30 - 6 = 6 - 6 = 0
Answer:
B
Step-by-step explanation:
Let's solve using factoring.
x²+5x-6=0
5 is the sum of the numbers, while -6 is their product.
Think: which two numbers add up to 5, but when multiplied, equal -6?
Those numbers are -1 and 6.
Now factor the polynomial:
(x-1)(x+6)=0
split into parts:
(x-1)=0
x-1=0
x=1
(x+6)=0
x+6=0
x=-6
So B
Hope this helps!
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.